2017
DOI: 10.1097/igc.0000000000000973
|View full text |Cite
|
Sign up to set email alerts
|

Combined Gene Therapy Using AdsVEGFR2 and AdsTie2 With Chemotherapy Reduces the Growth of Human Ovarian Cancer and Formation of Ascites in Mice

Abstract: Combined inhibition of VEGF/VEGFR2 and Ang/Tie2 pathways provided efficient therapy for ovarian cancer in mice. In addition, antiangiogenic gene therapy has potential as a treatment for the accumulation of ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
(32 reference statements)
2
9
0
1
Order By: Relevance
“…It has been shown that a combination of chemotherapy and gene therapy could be synergistically effective for cancer therapy ( Conde et al, 2016 ; Hu et al, 2017 ; Tuppurainen et al, 2017 ; Yang et al, 2017 ). To deliver plasmids carrying therapeutic genes into tumors, a choline derivative-modified co-delivery system has been evaluated which targets ChT; the system was used to deliver a plasmid encoding TRAIL (human tumor necrosis factor-related apoptosis-inducing ligand) and doxorubicin ( Li et al, 2013a ).…”
Section: Transporter-assisted Nano-drug Delivery Systemsmentioning
confidence: 99%
“…It has been shown that a combination of chemotherapy and gene therapy could be synergistically effective for cancer therapy ( Conde et al, 2016 ; Hu et al, 2017 ; Tuppurainen et al, 2017 ; Yang et al, 2017 ). To deliver plasmids carrying therapeutic genes into tumors, a choline derivative-modified co-delivery system has been evaluated which targets ChT; the system was used to deliver a plasmid encoding TRAIL (human tumor necrosis factor-related apoptosis-inducing ligand) and doxorubicin ( Li et al, 2013a ).…”
Section: Transporter-assisted Nano-drug Delivery Systemsmentioning
confidence: 99%
“…There is also evidence that a combined Tie-2 targeted gene therapy exerted an antitumor effect in animal models. Co-targeting of VEGFR1, -3 and Tie-2 has been associated with reduced growth of solid human ovarian cancer in mice, and furthermore, combined gene therapy using VEGFR2 and Tie-2 with chemotherapy has reduced the growth of tumors, as well as diminishing the formation of ascites in mice [31].…”
Section: Plos Onementioning
confidence: 99%
“…The survival is prolonged if PTX is added to combination gene therapy [ 86 ], being safe in healthy rats [ 87 ]. Furthermore, adenovirus gene therapy with soluble VEGFR2 and Ti2 reducing tumour growth and formation of ascities, enhanced reduction of ascities when gene therapy was combined with PTX and carboplatin, although in this last case, it increased the proliferation of tumour cells [ 88 ].…”
Section: Gene Therapy In Ovarian Cancermentioning
confidence: 99%